Mudharabah: Sustainable Sharia Investment Model - Beddu, Muhammad Juni; Eravia, Diana; Nulatifah, Nulatifah; Aslina, Neri; Ruhmah, Andi Amma; Addiningrum, Fitri Mehdini; Azhari, Muhammad Iqbal (STAI Auliaurrasyidin Tembilahan, 2023)
Mudharabah is a partnership between capital providers and entrepreneurs, where profits and risks are shared fairly in accordance with Islamic principles. This article aims to investigate the concept of Mudharabah as a sustainable investment model in the context of Sharia finance. A comprehensive review of the literature on Mudarabah and sustainable investment provides in-depth insight into the principles underlying both concepts. Regarding Mudarabah, this article examines its history, evolution and practical implementation in various economic sectors. On the other hand, sustainable investments are analyzed by considering social impacts, the environment and ethical considerations in making investment decisions. The findings of this research indicate that Mudharabah, as a sharia investment model, has significant potential in providing added value to society and the environment. Active participation in Mudharabah-based businesses can encourage economic empowerment, reduce disparities, and create opportunities for small and medium entrepreneurs.